HUBUNGAN TINGKAT STRES DAN POLA MAKAN DENGAN KEJADIAN DISPEPSIA PADA REMAJA DI SMA SEJAHTERA 1 DEPOK - Adelia Putri Fitriansyah (2020)
Dyspepsia is one of the digestive problems that occurs in the adolescent population. Dyspepsia occurs due to several trigger factors, such as stress and eating patterns. Dyspepsia has symptoms such as nausea, vomiting, satiety, frequent belching, abdominal pain, weight loss, to bleeding. The purpose of this study was to determine the relationship of stress levels and eating patterns with the incidence of dyspepsia in adolescents at SMA Sejahtera 1 Depok. The method used in this research is descriptive analytic with cross-sectional approach using probability sampling and simple random sampling techniques. This study uses univariate analysis to determine the frequency distribution and the average and bivariate analysis using the chi square test. The results of the study between the level of stress with the occurrence of dyspepsia have a p-value of 0,000 which indicates there is a relationship, while between eating patterns with the occurrence of dyspepsia have a p-value of 1,000 which indicates no relationship. The results of this study are expected to be a source of information for adolescents to implement healthy lifestyles by minimizing the occurrence of stress and eating well according to balanced nutrition guidelines so as to avoid the incidence of dyspepsia.